Dimeljska bolečina pri športnikih - Kolar, Jure (Šport (Ljubljana), 2017)
Groin pain is for its heterogenous nature usually referd as groin pain syndrome. Difficulty of injury slowly arises to a level when an athlete is no longer capable of taking part in competitive process. In groin region muscles of trunk and muslces of lower limb intertwine and insert to a pelvic. With agressive contractions and different role at the hip joint they apply a lot of mechanical loads in various directions, causing degenerative changes in tissues. In most cases pain is related to the adductor group, especially in tendon or enthesis at their origin at anterior and inferior part of pubic or tuberosity of the ischium. The article presents brief description of ethiopathogenesis of the injury, and review of pasive and active physical therapy. We also compared the effectivness of conservative therapy and surgical intervention.
Keywords: dimeljska bolečina; groin pain; mechanotransduction; mehanotransdukcija; prevention; preventiva; rehabilitacija; rehabilitation; sport; šport; športniki